SECONDARY SCHOOL STUDENTS ATTITUDE TOWARDS JUNIOR SCHOOL CERTIFICATE (JSC) EXAMINATION IN BANGLADESH - Rahman, MD. Mehadi (UPI Press, 2019)
The study investigates secondary students’ attitude towards junior school certificate (JSC) examination in Bangladesh. The study is mainly quantitative and data was collected in a computable manner through questionnaires. Secondary students who would take the JSC examination were the main data source of the study. Two hundred fifty students (120 male and 130 female) were chosen randomly from ten secondary schools (five private and five government) in Dhaka. The study revealed that secondary students have a positive attitude towards JSC examination. There was no significant difference between male and female students’ attitude towards JSC examination. JSC exam had increased students’ both quality of study and study time, enhanced students’ creativity, and reduced the fear of examination. On the contrary, JSC examination had hampered students’ normal life by extra stress, reduced their playtime, and made them dependent on guidebooks for better grades. Therefore, the study suggests changing current JSC examination systems by creating test items focused on creativity and problem-solving tasks to ensure the quality of education in Bangladesh. These findings can inform the government as well as other relevant stakeholders in making necessary changes in the JSC examination in Bangladesh.